THE EFFECTS OF QAR STRATEGY, DATA CHART STRATEGY, AND CRITICAL THINKING ON READING COMPREHENSION ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF SMK NURUL IMAN PALEMBANG - USWATUN TOIYIBAH (Sriwijaya University Learning and Education International Conference, 2016)
on reading comprehension achievement of the tenth grade students of SMK Nurul Iman Palembang. The method used in this study was factorial design. Fifty students of the tenth grade students of SMK Nurul Iman Palembang were selected as the sample in this study based on some criteria, namely, they were on the same reading level (level 3), were on the same level of critical thinking (high= 9 students, medium= 7 students, and low = 9 students) for each group, and taugth by the same English teacher. The instruments used were (1) reading comprehension test, and (2) critical thinking test. In analyzing the data, two statistical analyses were used: (1) independent sample t-test, and (2) two way ANOVA. The result of the study showed that there was no significant difference in reading comprehension between the students who were taught using QAR strategy and data chart strategy (t-value= -.171, ῤ= .865). Besides, there was a significant interaction effect between QAR strategy and students’ critical thinking level on reading comprehension achievement (ῤ= .034, (<0.05). Meanwhile, there was no interaction effect between data chart strategy and critical thinking (ῤ= .998 ).